Iceland : Stand-By Arrangement; Interim Review Under the Emergency Financing Mechanism. (IMF Staff Country Reports; Country Report ;, 2009)
This paper describes the Stand-By Arrangement for Iceland under the Emergency Financing Mechanism. The crisis is producing a sharp contraction of economic activity. Indicators of consumption are plummeting, and the deterioration in the labor market is accelerating, with rising unemployment and falling real wages contributing to a considerable contraction in real incomes. Significant import compression is under way, allowing a sustained turnaround in the trade balance, as exports continue to benefit from a weaker krona. The krona interbank market is inactive, and equity markets remain under pressure with trade being thin.